Relevância da dimensão cultural na pesquisa educacional: uma proposta de transversalidade - Roseli Fischmann (EccoS – Revista Científica)
This paper proposes a reflection on the cultural dimension as a kind of transverse theme in educational research. This transversality has an epistemological and methodological meaning, supported by an ethical basis. It is an approach that goes through epistemological paths which inevitably touch the inequality and exclusion theme when dealing with the field of cultural differences. Along this path cultural plurality and education are privileged, bringing to reflection epistemological obstacles emerged mostly from ignorance and disregard concerning cultural dimension, what may have compromised the results of educational researches in many fields. It is also emphasized the urgently necessity of including in researches and teachers formation the singular contribution brought by the comprehension of the cultural plurality phenomenon in its multiple manifestations